Clinical profile of patients with COVID-19 and tuberculosis co-infection in a tertiary care hospital - B., Karthik Adiga; B. L., Shashibhushan; A. S., Deepa (International Journal of Research in Medical Sciences, 2022)
Background: Historical evidences suggest that Tuberculosis (TB) with concurrent respiratory viral infections, such as, Influenza has been associated with higher mortality. TB and COVID-19 co-infection has implications beyond mortality at the individual level. Hence there is a need to study the clinical characteristics and outcomes in COVID-19 and TB co-infection. Methods: In this retrospective observational study, COVID-19 cases admitted to Victoria Hospital, a tertiary care hospital in Bengaluru, twenty-six patients with COVID 19 and TB co-infection were observed and their clinical characteristics, radiological and laboratory parameters were recorded and analyzed for the impact of COVID-19 on TB. Results: Raised inflammatory markers, high neutrophil to lymphocyte ratio (NLR), lymphocytopenia were observed in majority of the cases. There was worsening of Tubercular lesions on Chest radiography in eighteen patients (69%). Out of the twenty six, sixteen patients (61%) needed supplemental oxygen therapy at admission, Five (19%) of them needed Assisted ventilation and intensive care. Out of the five patients who needed intensive care, two (7.6%) patients succumbed to death owing to Severe COVID-19 pneumonia, respiratory failure and other co-morbid conditions. Conclusions: Co-infection with COVID-19 and TB alters the severity, the course and management of the disease and can be associated with adverse outcomes and is associated with high mortality; a high index of suspicion is required for the detection of this co-infection and bi-directional screening of COVID-19 and TB must be carried out for the early detection and management of this co-infection.